Pluripotent stem cell strategies for rebuilding the human brain - Limone, Francesco; Klim, Joseph R.; Mordes, Daniel A. (Frontiers in Aging Neuroscience, 2022)
Neurodegenerative disorders have been extremely challenging to treat with traditional drug-based approaches and curative therapies are lacking. Given continued progress in stem cell technologies, cell replacement strategies have emerged as concrete and potentially viable therapeutic options. In this review, we cover advances in methods used to differentiate human pluripotent stem cells into several highly specialized types of neurons, including cholinergic, dopaminergic, and motor neurons, and the potential clinical applications of stem cell-derived neurons for common neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, ataxia, and amyotrophic lateral sclerosis. Additionally, we summarize cellular differentiation techniques for generating glial cell populations, including oligodendrocytes and microglia, and their conceivable translational roles in supporting neural function. Clinical trials of specific cell replacement therapies in the nervous system are already underway, and several attractive avenues in regenerative medicine warrant further investigation.